INTRANET SISTEM INFORMASI AKADEMIK STMIK AUB SURAKARTA BERBASIS MAC ADDRESS UNTUK AUTO LOGIN - Jamal Nasirudin STMIK AUB; H. Ary Setyadi STMIK AUB (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2018)
ABSTRACT - Every college in general have limitations in data processing students' academic information system with the amount of human resources are limited data processing serve much the student data . Some of these limitations is a data processing course registration will be taken by students or retrieval Card Study Results ( KHS ) and manufacture of Study Result Card ( KHS ) . There are still many who use the system manual process . Making the academic information system application Surakarta STMIK AUB -based mac address utilizes the PHP programming language and MySQL database research method using descriptive method .It is expected that the system is able to provide a security system in the development of the previous system helps the staff STMIK AUB Surakarta KRS and KHS process more efficient . Keywords : Processing Value , Study Plan Card , Card Study Results , STMIK AUB Surakarta